LB0003 EFFICACY AND SAFETY OF FILGOTINIB FOR PATIENTS WITH RHEUMATOID ARTHRITIS NAïVE TO METHOTREXATE THERAPY: FINCH3 PRIMARY OUTCOME RESULTS. (June 2019) - Westhovens, Rene; Rigby, William; van der Heijde, Désirée; Ching, Daniel; Bartok, Beatrix; Matzkies, Franziska; Yin, Zhaoyu; Guo, Ying; Tasset, Chantal; Sundy, John; Mozaffarian, Neelufar; Messina, Osvaldo; et al.
Abstract : Background: Filgotinib (FIL), an orally administered, potent, selective inhibitor of Janus kinase 1 (JAK1), has shown good efficacy and was well tolerated for treatment of rheumatoid arthritis (RA). Objectives: To compare efficacy and safety of FIL with and without methotrexate (MTX) in patients with RA who were naïve to MTX therapy. Methods: This phase 3, double-blind, active-controlled study randomized patients with moderately to severely active RA (2:1:1:2) to FIL 200mg daily + MTX weekly (up to 20mg), FIL 100mg + MTX, FIL 200mg (+placebo [PBO]), or MTX (+PBO) for up to 52 weeks; results through week 24 are presented. Primary efficacy endpoint was proportion of patients achieving ACR20 response at week 24; additional assessments included ACR50 and ACR70 responses; DAS28-CRP score ≤3.2 and <2.6, and changes in van der Heijde mTSS, HAQ-DI, SF-36 PCS, and FACIT-Fatigue. Safety endpoints included types and rates of adverse events (AEs). Logistic regression adjusting for stratification factors with nonresponder imputation was used for treatment comparisons for ACR response and other binary endpoints. Mixed-effect model adjusting for baseline value, stratification factors, treatment, visit, and treatment by visit interaction as fixed effects with observed cases was used for continuous endpoints. Results: Of 1, 252 randomized patients, 1, 249 received study drug (416 FIL 200mg+MTX; 207 FIL 100mg+MTX; 210 FIL 200mg monotherapy; 416 MTX monotherapy) and were analyzed; 1, 130 completed week 24. Most (76.9%) were female; mean time since RA diagnosis was 2.2 years (median 0.4 years); mean (standard deviation [SD]) DAS28-CRP was 5.7 (1.0); and 35.9% were using oral steroids at baseline. At week 24, significantly more patients in the FIL 200mg+MTX (81.0%; P <0.001) and FIL 100mg+MTX (80.2%; P <0.05) arms achieved an ACR20 response compared to MTX monotherapy (71.4%)(Table 1). Compared to MTX monotherapy, more patients receiving FIL with or without MTX achieved ACR50 and ACR70 responses, DAS28-CRP <2.6 and ≤3.2, and reported improvements in SF-36 PCS (Table 1). The onset of activity was rapid, with significantly more patients achieving ACR50 and DAS28-CRP <2.6 with FIL than MTX at week 2. The FIL safety profile was consistent with prior studies through week 24 (Table 2). Conclusion: The JAK1 inhibitor FIL in combination with MTX led to significant improvements in RA signs and symptoms, physical function, and patient-reported outcomes compared to MTX alone and was well tolerated in patients with early active RA naïve to MTX. Clinically meaningful response to FIL occurred as early as 2 weeks after treatment initiation. Disclosure of Interests: Rene Westhovens Grant/research support from: Celltrion, Galapagos/Gilead, Consultant for: Celltrion, Galapagos-Gilead, William Rigby Consultant for: Gilead, Désirée van der Heijde Consultant for: AbbVie, Amgen, Astellas, AstraZeneca, Bristol-Myers Squibb, Boehringer Ingelheim, Celgene, Daiichi, Eli-Lilly, Galapagos, Gilead, GlaxoSmithKline, Janssen, Merck, Novartis, Pfizer, Regeneron, Roche, Sanofi, Takeda, Union Chimique Belge, Daniel Ching Speakers bureau: AbbVie, Beatrix Bartok Shareholder of: Gilead, Employee of: Gilead, Franziska Matzkies Shareholder of: Gilead, Employee of: Gilead, Zhaoyu Yin Shareholder of: Gilead, Employee of: Gilead, Ying Guo Shareholder of: Gilead, Employee of: Gilead, Chantal Tasset Shareholder of: Warrants from Galapagos, Employee of: Galapagos, John Sundy Shareholder of: Gilead Sciences, Inc., Employee of: Gilead Sciences, Inc., Neelufar Mozaffarian Shareholder of: Gilead, Employee of: Gilead (former employee), Osvaldo Messina Consultant for: Consultant for Eli Lily, Amgen, Pfizer, and Americas Health Foundation., Robert B.M. Landewé: None declared, Tatsuya Atsumi Grant/research support from: Astellas Pharma Inc., Takeda Pharmaceutical Co., Ltd., Mitsubishi Tanabe Pharma Co., Chugai Pharmaceutical Co., Ltd., Daiichi Sankyo Co. Ltd., Otsuka Pharmaceutical Co., Ltd. and Pfizer Inc. Alexion Inc., Bayer Yakuhin, Ltd, Otsuka Pharmaceutical Co., Ltd. Chugai Pharmaceutical Co., Ltd., Takeda Pharmaceutical Co., Ltd., Eisai Co., Ltd., Bristol-Myers Squibb Co., Daiichi Sankyo Co. Ltd., Mitsubishi Tanabe Pharma Co., Asahi Kasei Pharma Co., Consultant for: ONO PHARMACEUTICAL CO., LTD Sanofi K.K. Daiichi Sankyo Co., Ltd. Pfizer Inc., Speakers bureau: Mitsubishi Tanabe Pharma Co., Chugai Pharmaceutical Co., Ltd., Astellas Pharma Inc., Takeda Pharmaceutical Co., Ltd., Pfizer Inc., Daiichi Sankyo Co. Ltd., Bristol-Myers Squibb Co., Eli Lilly Japan K.K., Gerd Rüdiger Burmester Consultant for: Roche, Sanofi-Genzyme, Speakers bureau: Roche, Sanofi-Genzyme